2007
DOI: 10.1097/sla.0b013e318155a789
|View full text |Cite
|
Sign up to set email alerts
|

Tight Glycemic Control in Critically Injured Trauma Patients

Abstract: The positive outcomes associated with the implementation of a TGC protocol necessitates further evaluation in a randomized prospective trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 14 publications
2
66
0
1
Order By: Relevance
“…This was associated with greater in-hospital mortality, longer hospital stays, and increased rates of admission to the ICU. Additionally, the general trauma and critical care literature is replete with investigations on the relationship of hyperglycemia with morbidity and mortality following critical illness [9][10][11][12]15,16 , with some authors suggesting that ongoing persistent hyperglycemia and subsequent glucose control are predictive of outcome 21,24 . However, this has not been easily translated into results that may be applied in an environment outside of an ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was associated with greater in-hospital mortality, longer hospital stays, and increased rates of admission to the ICU. Additionally, the general trauma and critical care literature is replete with investigations on the relationship of hyperglycemia with morbidity and mortality following critical illness [9][10][11][12]15,16 , with some authors suggesting that ongoing persistent hyperglycemia and subsequent glucose control are predictive of outcome 21,24 . However, this has not been easily translated into results that may be applied in an environment outside of an ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated perioperative serum blood glucose levels in general surgery patients increase the risk of postoperative infections, independent of diabetic status 7,8 . While the authors of numerous studies have investigated the effect of hyperglycemia in patients with critical illness [9][10][11][12] , few have commented on the impact of acute hyperglycemia in patients who are not in the ICU.…”
mentioning
confidence: 99%
“…They found a significant reduction in mortality of patients in surgical ICU with IIT and advised the same. Subsequent studies reported significant benefits of IIT and reinstated the previous existing guidelines [13][14][15][16]. However, this has been challenged by many studies conducted over the past few years which have found increased incidence of complications with IIT, especially hypoglycemic episodes and have recommended following a protocol base approach in glucose control after trauma and in critically ill patients to achieve optimal results, rather than IIT [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 96%
“…1,2,5,8,[14][15][16][18][19][20][31][32][33][34][35][36] Our team and others have previously demonstrated the association between malglycemia (hyperglycemia, hypoglycemia and increased glycemic variability) and increased NRM and infections in HCT patients. [24][25][26] In addition, adverse clinical consequences of hyperglycemia from total parenteral nutrition exposure during HCT were reported.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Recently, efforts have been made to control hyperglycemia during hospitalization, but results from clinical trials and retrospective analyses have demonstrated inconsistent outcomes associated with intensive insulin therapy. [4][5][6][7][8][9][10][11][12] There is also evidence that severe hypoglycemia (glucose o40 mg/dL) in hospitalized patients may have a detrimental effect on outcomes, including cardiac arrest, seizures, hypoglycemia-induced coma and mortality, 5,[13][14][15][16][17] thus limiting the efforts for meticulous glucose control in the hospital. In addition, recent evidence also suggests that glucose variability can be detrimental and increase mortality risk in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%